PERBEDAAN EFEKTIVITAS CONSTRUCTED WETLANDSSUBSURFACE FLOW SYSTEM DAN FREE WATER SURFACE PADATANAMAN CATTAIL UNTUK MENURUNKAN BOD, COD dan FOSFAT LIMBAH LAUNDRY DI KELURAHAN TEMBALANG, KOTA SEMARANG - Miftah Hermaning Putri; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2016)
Small laundry industry is activities that related in laundering services. Laundry wastewater directly disposed into sewerage without treatment. The checking result of BOD, COD and phosphate of laundry waswater is 260,3 mg/l, 832,9 mg/l, and 10,83 mg/l this number is exceed the standard of Perda Jateng No 5 2012 th. The study research is using quasi experiment (quasi experiment) with pre test - post test design.The research objects are the laundry liquid wastes from "Rahma" laundry, "Zone" laundry, and "Pelangi" laundry. The analysis of data using different test Independent t-test for normal distribution of data. The levels of BOD, COD, and phosphate pre experiment of using subsurface flow system was 260,25 mg/l; 823,938 mg/l; 10,8973 mg/l. And the levels of BOD, COD, and phosphate post experiment of using subsurface flow system had decreased 29.0625 mg/l; 80.5625 mg/l; 4.556 mg/l.  While the levels of BOD, COD and phosphate pre experiment of using free water surface is 260.25; 823.938, 10.83, and post treatment had decreased to 58.8125 mg/l; 160.375 mg/l; 7,545 mg/l. The levels of BOD, COD and phosphate with subsurface flow system treatment decreased 87.22% BOD; COD 87.81%; and Phosphate 59.2%, while the decrease from the free water surface treatment was BOD 74.89%; COD 76.54%; and phosphate 30.55%. The different test result of BOD(Sig 0,001), COD (Sig 0,001) and Fosfat (Sig 0,002) shows there are an average difference beetween effectiveness differences constructed wetlands subsurface flow system and a free water surface on cattail plants to reduce the number of BOD levels, COD levels, and phosphate levels of laudry wastewater.